Threat, savior, or victim? How Ukrainian online news media represent labor migrants during Russia’s aggression against Ukraine - Palagnyuk, Yuliana (Przegląd Wschodnioeuropejski, 2025)
The socio-economic crisis in Ukraine after the start of Russia’s aggression against Ukraine in 2014 and Ukraine’s signing of the Association Agreement with the EU increased labor migration from Ukraine to EU member states. Based on the application of A. Tymczuk’s model of media frames regarding Ukrainian labor migrants, and using a qualitative thematic and frame analysis of selected online news media in Ukraine, I conclude that the media represent the Ukrainian labor migrant as a “threat” to the economic situation of Ukraine, and as a “savior” for the economies of their host countries in the EU. At the same time, there is less media representation of Ukrainian labor migrants as a “victim” of the difficult internal situation in their country or in their host countries. This conclusion corroborates the academic debate on Ukrainian labor migration by addressing positive and negative aspects of external labor migration.